Cognitive fatigue and its effects on choice reaction time in elite Muay Thai athletes - Chew, Yan Ying (Nanyang Technological University, 2021)
Background: Choice Reaction Time (CRT) is a key component in Muay Thai. Swift and accurate decision making accompanied by fast reaction time allows a fighter to execute strikes that lead to his or her success in a fight. Fighters in Singapore are often subjected to cognitive fatigue (interchangeably known as mental fatigue), as majority work before training. There has been several studies conducted to research on the effects of mental fatigue on physical performance, but few on effects of mental fatigue and decision making and reaction time. Aim: The aim of this study was to induce cognitive fatigue into elite Muay Thai athletes and analyse its possible effects on CRT. Methods: 18 elite Muay Thai fighters were recruited and completed both a mentally fatiguing task and a control task on two separate occasions, and the Stroop Test was used evaluate their CRTs. In addition, a self-administered questionnaire, the Mental Fatigue Score was also given to participants to assess their mental fatigue levels. Results: Results obtained from the Stroop Test were compared using Two-way Repeated ANOVA while scores from the questionnaire were compared using Friedman’s Test. Conclusion: Findings from this study showed significant results, indicating that cognitive fatigue causes negative effects on CRT. Limitations: Future studies should include the use of a better control or induce cognitive fatigue more aggressively for better significant results.